2013
DOI: 10.17221/100/2012-agricecon
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contract farming on the U.S. crop farmers' average return

Abstract: Abstract:In the literature of contract farming, most of the studies focus on the functions of risk managements and reducing transaction costs. Only a few study the eff ect of contract farming on the productivity effi ciency or profi tability. Literature in the crop sector is especially lacking. In this paper, we use a unique farm-level dataset (Agricultural Resource Management Survey from the U.S. Department of Agriculture) to examine the eff ect of contract farming on the farmers' average return for the corn,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
6
11
0
Order By: Relevance
“…The implication of the results from the regression may be that CF has a positive effect on profitability of rice growers in the study area. This finding is also consistent with earlier studies by Mishra, et al (2018), Hu (2013) and Bolwig et al (2009). Table 4 also reports the full regression results for different outcome indicators including average variable cost, selling price, average return and average rate of return.…”
Section: Estimated Effect Of Contract Farming On Profitability Of Ricsupporting
confidence: 88%
See 1 more Smart Citation
“…The implication of the results from the regression may be that CF has a positive effect on profitability of rice growers in the study area. This finding is also consistent with earlier studies by Mishra, et al (2018), Hu (2013) and Bolwig et al (2009). Table 4 also reports the full regression results for different outcome indicators including average variable cost, selling price, average return and average rate of return.…”
Section: Estimated Effect Of Contract Farming On Profitability Of Ricsupporting
confidence: 88%
“…Many studies show that contract farming improve largely farm productivity and households income or welfare such as those by Girma and Gardebroek (2015), Naryananan, (2014), Dedehouanou et al (2013), Cahyadi and Waibel (2013), Bellemare (2012), Maertens and Swinnen (2009), Miyata et al (2009), Minten et al (2009), and Bolwig et al (2009). However, few studies have estimated the effect of CF on profitability (Hu, 2013). In addition, most CF studies have examined high-value products including industrial crops, horticulture, poultry, and dairy, but rarely staple foods (Maertens and Velde, 2017;Minot, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…The negative effect on technical efficiency may be attributed among other factors to increased input prices and harvesting of canes before maturity. On the contrary, the results by Hu (2013) and Igweoscar (2014) showed a positve and significant effect of contract engagement on technical efficiency. This variable therefore needs more investigation since farmers enter into contract engagement with the aim of increasing their productity which the current study has revealed otherwise.…”
Section: Factors Affecting Technical Efficiency Among Sugarcane Farmersmentioning
confidence: 88%
“…In terms of contract farming, PSM is used to investigate infl uences of contract farming on crop productivity and income of farmers (Ragasa et al, 2018;Mulatu et al, 2017;Mwambi et al, 2016;Hu, 2013).…”
Section: Theoretical and Empirical Frameworkmentioning
confidence: 99%